Kajian Hukum Ekonomi Syariah dalam Penyelesaian Wanprestasi Praktik Jual Beli Kayu Jati secara Kredit pada Usaha Dagang Berkah Jati Mlonggo Jepara - Salsabilla, Sherly Nur; Aristoni, Aristoni (Sharia Faculty Islamic Economic Law Study Department, 2023)
Problems with business activities often end in conflict because one of the parties defaults or does not fulfill the obligations agreed together. This research aims to determine the resolution of defaults in the practice of buying and selling teak wood at the Berkah Jati Mlonggo Jepara Trading Business and analyze it using a Sharia Economic Law approach. The type of method used in this research is field research based on a sociological juridical approach. To obtain information or data, this research uses data sources in the form of primary data and secondary data. Primary data was obtained by direct interviews with informants or sources, while secondary data consisted of primary legal materials, secondary legal materials, and tertiary legal materials. After the information or data is collected, analysis is then carried out using qualitative descriptive data analysis techniques. The findings of this research indicate that the practice of buying and selling teak wood is carried out in writing using a cash and credit payment system. The credit practices carried out by sellers follow Sharia principles, meaning there is no element of usury. Resolving defaults through negotiation by providing several offers to extend the payment period (rescheduling) and relief from credit installment payments (reconditioning). The realization of default resolution in the practice of buying and selling teak wood in the study of Sharia Economic Law is the seller's effort to create benefits and avoid mafsadah so that the relationship between the seller and the buyer remains harmonious and can avoid hostility.